Combination effects of rubber and silica fume on the fracture behaviour of steel-fibre recycled aggregate concrete. (10th April 2019) - Xie, Jianhe; Li, Jianglin; Lu, Zhongyu; Li, Zhijian; Fang, Chi; Huang, Liang; Li, Lijuan
Highlights: Coupling effects of rubber and silica fume on fracture behaviour of steel-fibre RAC were studied. Adding silica fume and steel fibre provides excellent fracture resistance in rubberized RAC. The replacement of 10% cement by silica fume is superior to the addition of 3% silica fume. Combination usage of 5% rubber and 10% silica fume content is recommended for steel-fibre RAC. Abstract: The use of recycled concrete aggregate and crumb rubber in structural concrete is a sustainable way to reduce the detrimental impacts of solid waste on the environment and address the shortage of natural resources. For the safe and economical design of rubberized steel-fibre recycled aggregate concrete (RSRAC), the mechanical behaviour of RSRAC modified with silica fume needs to be properly understood. In the present study, the coupling effects of crumb rubber and silica fume on the fracture behaviour of RSRAC were examined for the first time. The results from a series of tests on a notched beam and cylinder under three-point bending and compression, where the RSRACs were incorporated with crumb rubber with a volume substitution of fine aggregate by 0%, 5%, 10%, 15% and 20%, are presented and discussed. The results indicated that the combination of rubber and silica fume exhibited excellent coupling effects on the fracture performance of RSRAC. Regarding reducing the negative effects of rubber, the replacement of 10% cement by silica fume was superior to the addition of 3% silica fume. When considering the mechanical improvement, the RSRAC with 5% rubber and 10% silica fume seems to be a more environmentally friendly material compared with normal concrete for structural elements.